Treatment of Slack Wax by Thermal Cracking Process - A.K Mohammed, Abdul Halim; Mohammed Obeyed, Saleem (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
This work deals with thermal cracking of slack wax produced as a byproduct from solvent dewaxing process of medium lubricating oil fraction in AL-Dura refinery. The thermal cracking process was carried out at a temperature ranges 480-540 ºC and atmospheric pressure. The liquid hourly space velocity (LHSV) for thermal cracking was varied between 1.0-2.5 . It was found that the conversion increased (61 - 83) with the increasing of reaction temperature (480 - 540) and decreased (83 - 63) with the increasing of liquid hourly space velocity (1.0 - 2.5). The maximum gasoline yield obtained by thermal cracking process (48.52 wt. % of feed) was obtained at 500 ºC and liquid hour space velocity 1 . The obtaining liquid product at the best operating condition 500 ºC and LHSV 1 was fractionated into wide range fractions. Based on the determination of some properties for the distilled fractions and comparison (these properties with that required by standard requirements) it is possible to use the fractions of cracking products as a component for production of automobile gasoline, domestic kerosene, light diesel fuel and basic lubricating oils.